The Validity of Oral Land Buying and Selling According to Indonesian Positive Law - Siti Misnar Abdul Jalil; Guswan Hakim; Ni Nyoman Triana Suskendariani (Jurnal Restorasi : Hukum dan Politik, 2026)
Land buying and selling is a legal act with significant legal consequences because it relates to land rights protected by the state. In practice, particularly in rural areas, land buying and selling is still frequently conducted orally based on local beliefs and customs. The question that arises is whether such oral land buying and selling is valid under Indonesian positive law and how strong its evidence is in the event of a dispute. This study aims to analyze the validity of oral land buying and selling from the perspective of civil law, the Basic Agrarian Law, and its implementing regulations. The research method used is normative juridical with a statutory and conceptual approach. The results indicate that oral land buying and selling, in principle, does not meet the formal requirements stipulated by statutory regulations and therefore does not provide legal certainty, although under customary law, land buying and selling can be conducted orally. Therefore, land buying and selling must be conducted in writing before a Land Deed Official (PPAT) to ensure legal certainty and protection for the parties.